2013
DOI: 10.1590/s0100-83582013000300022
|View full text |Cite
|
Sign up to set email alerts
|

Volumes de calda e adjuvante no controle de plantas daninhas com glyphosate

Abstract: RESUMO -O sucesso de uma aplicação de herbicida está diretamente relacionado a uma boa deposição da calda no alvo, com o mínimo de perdas para o ambiente. Assim, o presente trabalho objetivou avaliar a deposição e o controle de plantas daninhas promovido pela aplicação de glyphosate em diferentes volumes de calda e com a adição do adjuvante nonil fenol etoxilado. O experimento foi conduzido em delineamento de blocos casualizados com quatro repetições, em esquema fatorial 3x2, sendo três volumes de calda (30, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…This demonstrates the possibility of reducing the application volume with the use of nozzles which provide an ultra-coarse droplets size category with induction of air due to having lower losses by drift compared to fine and very fine droplets (Chechetto et al, 2013). 1 Glyphosate at the dose of 0.975 kg ha -1 of acid equivalent + antifoaming at the concentration of 0.0025% of v/v.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This demonstrates the possibility of reducing the application volume with the use of nozzles which provide an ultra-coarse droplets size category with induction of air due to having lower losses by drift compared to fine and very fine droplets (Chechetto et al, 2013). 1 Glyphosate at the dose of 0.975 kg ha -1 of acid equivalent + antifoaming at the concentration of 0.0025% of v/v.…”
Section: Resultsmentioning
confidence: 94%
“…The droplet size combined with the application volume and products diluted in the spray mix may influence the distribution and deposition quality of products. Researchers in the phytosanitary area have been working to verify the possibility of reducing the application volume in agricultural sprays with different classes of phytosanitary products as herbicides (Ferreira et al, 1998;Bracamonte et al, 1999;Garcia et al, 2004;Rodrigues et al, 2011;Bueno et al, 2013;Almeida et al, 2014), insecticides (Bonadiman, 2008;Maziero et al, 2009;Pereira et al, 2012) and fungicides (Meneghetti 2006;Oliveira, et al, 2007;Cunha and Silva Júnior, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, drift potential should also be evaluated using lower carrier volumes. Bueno et al (2013) evaluated the effects of spray volumes and adjuvants on weed control using glyphosate sprayed through Turbo Teejet nozzles (TT 11002). The authors also observed similar glyphosate efficacy at 30, 60, and 150 L ha -1 , with or without the adjuvant nonyl phenol ethoxylate in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the chemical control method is the most used to inhibit the growth of invasive plants, which includes the use of synthetic herbicides, in large quantities, mainly by large producers, as reported by some authors [20,21]. The use of synthetic and toxic chemical herbicides in management areas promotes the death of weeds in a selective way and, consequently, it ends the competition among the plants, helping to increase the production of green mass in the pasture [22].…”
Section: Control Of Invasive Plantsmentioning
confidence: 99%